Obstetric Management of a Patient with Narcolepsy and Cataplexy: A Case Report - S. Ajayi; R. Kinagi; E. Haslett (Case Reports in Obstetrics and Gynecology)
We report the management of a patient who suffers from narcolepsy and cataplexy and presented to the clinic at 14 weeks of gestation. Her symptoms were resistant to modafinil but controlled with clomipramine and amphetamine. Discussion concerning mode of delivery for these patients is scarce in the literature. We discuss some issues surrounding the antenatal management and counselling regarding mode of delivery and postpartum care.